A Prática pedagógica sob o olhar do professor bacharel : o caso de um ensino médio integrado do IFG - (:unkn) unknown (Universidade Estadual de Goiás, 2018)
This dissertation, linked to Research Line Education, School and Technologies of the Interdisciplinary Postgraduate Program in Education, Language and Technologies of the State University of Goiás, expresses as general objective the bachelors teachers pedagogical practice of a Campus of the Federal Institute of Goiás - IFG. Regarding the specific objectives, this work proposes to carry out studies on the history, principles and guiding concepts of Technical Professional Education and to observe if these conceptions are reflected in the pedagogical practice of these bachelors; understand how these teachers conceive the relation Education and Work in their pedagogical practices; and finally, to identify whether the bachelors pedagogical practice contemplate a critical approach in the teaching and learning process and the principles of polytechnic education. In order to develop studies about the principles of Professional Education, its historical and philosophical conceptions and the reflection about the Integrated Technician to High School, it was essential the writings of Machado (1982, 1991, 2006), Fonseca (1961), Cunha (2000, 2005) (2003), as well as other authors such as Marx and Engels (2001) and Gramsci (2001) 1979, 2000). In order to understand the fundamentals of pedagogical practice and the critical approach to teaching, we read Veiga (1992), Tardif (2002, 2014), Pimenta (1998), Figueiredo (2006) and Vygotsky (2007). The perspective used as a reference in our research is dialectical historical materialism because it provides a view of the totality of the real. This research is characterized as a qualitative case study, whose corpus of analysis is constituted by 14 bachelors without continuous pedagogical training that work in Technical Courses Integrated to the High School of a Campus of the IFG. In view of this study, it was evidenced that approximately 62% of the bachelors of this Campus of the IFG signal a pedagogical practice guided by the guidelines of the Polytechnic Education. Referring to teachers' understanding of the Education and Work relationship, we consider that about 50% of graduates still have their conceptions with greater emphasis on the labor market, and that about 50% of graduates conceive of this relation Education and Work through the "Work as an educational principle". We also show that, in the observed criteria related to elements of critical theory (foundation by the Sociocultural Theory - ZPD, Scaffolding and Mediation), the bachelors reach a percentage above 60% of indicative of presence of this theory in their pedagogical practices. So, up the numbers, we consider that the pedagogical practice of these bachelors has indications of the guidelines of the Polytechnic Education, which, in turn, have a critical, reflexive education, focused on Integral/Omnilateral Human Formation and has some characteristics that align to Sociocultural Theory. Thus, on the basis of this assumption, the bachelors present, even in a "fragmented" way, a pedagogical practice that includes elements of Polytechnic Education and the Sociocultural Approach that could have them in a consolidated and/or "complete" case there would be continued training that would encompass the teaching about these practices/elements.
Keywords: Professor Bacharel; Educação Profissional Técnica; Prática Pedagógica; Ensino Médio Integrado; Insituto Federal de Goiás; Professor Bachelor; Technical Professional Education; Pedagogical Practice; Integrated Secondary Education; Federal Institute of Goias; CIENCIAS HUMANAS::EDUCACAO